Penggunaan Media Gambar Rumah Adat Jawa Tengah Untuk Mengenalkan Bangun Datar pada Pembelajaran Matematika Siswa Kelas 2 - SETIYANI, YULI (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
The use of learning media for traditional Javanese traditional houses in mathematics learning of flat-build material selected by teachers in class 2 MI MA'ARIF NU 2 SANGGREMAN results showed an increase in learning activities both in terms of activities and learning outcomes. This research is a case study research. The activity shows during the implementation of learning activities motivation, interest, activity, involvement, and enthusiasm of students to learn in the